Leptosphaeria spp., phoma stem canker and potential spread of L. maculans on oilseed rape crops in China. (21st November 2013) - Zhang, X.; White, R. P.; Demir, E.; Jedryczka, M.; Lange, R. M.; Islam, M.; Li, Z. Q.; Huang, Y. J.; Hall, A. M.; Zhou, G.; Wang, Z.; Cai, X.; et al.
<x xml:space="preserve">Abstract</x> In China, the incidence of phoma stem canker observed in pre‐harvest surveys from 2005 to 2012 was greater on winter oilseed rape in provinces in central China (in May) than on spring oilseed rape in north China (in August). In all 742 cases when the causal pathogen was isolated from stem cankers, it was identified as Leptosphaeria biglobosa by morphology in culture and/or by species‐specific polymerase chain reaction. Both L. biglobosa and Leptosphaeria maculans were detected on crop debris and seed in shipments of oilseed rape seed imported into China through Shanghai or Wuhan ports in 2009–2011. Descriptions of the observed spread of L. maculans into areas previously colonized by L. biglobosa across a spring oilseed rape growing region (Alberta, Canada, westwards, 1984–1998) and across a winter oilseed rape growing region (Poland, eastwards, 1984–2004) were used to estimate the potential westward spread of L. maculans in China across spring oilseed rape growing regions (north China) and winter oilseed rape growing regions (central China, generally provinces along the Yangtze River), respectively. The rates of spread were estimated as 47 km per year across spring oilseed rape in north China and 70 km per year across winter oilseed rape in central China. Dispersal modelling suggested that the rate of spread of L. maculans across Alberta, Canada (c. 17 km per year) could be explained by windborne dispersal of ascospores.